PERBANDINGAN TOTAL SENYAWA FLAVONOID EKSTRAK ETANOL KULIT DAN BIJI BUAH OKRA HIJAU (Abelmoschus esculentus L.) - Yanti, Dharma; Putri, Indah Ananda (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
Green okra (Abelmoschus esculentus L.) is a plant belonging to the Malvaceae family. Green okra fruit contains many secondary metabolites, one of which is flavonoids, which have potential as antioxidants to stabilize free radicals. This study aims to determine and compare the total flavonoid content of seeds and skin, so that it can be ascertained which part of the fruit has the highest total flavonoid content. The okra fruit extraction process was carried out by maceration with 70% ethanol solvent. Phytochemical screening and thin layer chromatography tests were performed on green okra seeds and skin extracts. The total flavonoid content was determined using the colorimetric-aluminum chloride method with UV-Vis spectrophotometry. The results of the phytochemical screening showed that the ethanol extract of green okra fruit peels contained alkaloids, flavonoids, tannins, and steroids, while the ethanol extract of green okra fruit seeds contained alkaloids, flavonoids, saponins, and tannins. The results of the thin layer chromatography test showed that the ethanol extract of green okra fruit skin and seeds contained a flavonoid compound as quercetin. The results of the total flavonoid content of the ethanol extract of green okra fruit skin : okra fruit seeds were 6.4589 mg QE/g extract ± 0.86 : 27.7583 mg QE/g extract ± 0.36. Based on statistical results with an Independent T test using SPSS, the significance value (2-tailed) of both samples was < 0.05, which means that there is a real difference between the total flavonoid compounds of skin ethanol extract and ethanol extract of green okra fruit seeds.